Literature and the child : romantic continuations, postmodern contestations - McGavran, James Holt, Jr., 1941-2014 (University of Iowa Press, 1999)
These distinguished essays powerfully define the myriad ways in which the Romantic image of the child, so compellingly portrayed by Wordsworth and Blake, continues to haunt us, shaping contemporary visions of childhood from Calvin and Hobbes to postmodernist poetry and fiction to sociological discussions of child-labor, child-abuse and the feminization of poverty. Literature and the Child, ably edited by James Holt McGavran, should be read by anyone interested in the history of the cultural construction of childhood.--Anne K. Mellor.
Keywords: Children's literature, English -- History and criticism.; Children's literature, American -- History and criticism.; Children -- Books and reading.; Postmodernism (Literature); Romanticism.; Littérature de jeunesse anglaise -- Histoire et critique.; Littérature de jeunesse américaine -- Histoire et critique.; Enfants -- Livres et lecture.; Postmodernisme (Littérature); Romantisme.; romanticism (form of expression); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; SOCIAL SCIENCE -- Children's Studies.; Children -- Books and reading; Children's literature, American; Children's literature, English; Romanticism; Das Romantische; Jugendliteratur; Englisch.; Criticism, interpretation, etc.